Opiate processes in poultry - Sheehan, Melinda H. (Archives of Medical Science, 2009)
The chicken is one of the most common widespread domesticated animals in the world. We rely on them as a primary source of food and consume both their meat and eggs; therefore their overall health should be of great concern and relevance. In this regard, opioid peptide and opiate alkaloid processes in mammals and invertebrates have functions that transcend their actions as anti-nociceptive agents. Many reports document their presence and action in many different physiological processes, such as neural, immune, vascular and digestive systems. Since poultry are the closest living animals to dinosaurs we examined these animals to determine if they too had an endogenous opioid system that was diffuse in function and presence. Indeed, poultry contain such an opioid system, which includes many physiological systems beside neural processes involved in pain perception. In this assessment it was also discovered that poultry opioid processes display novel idiosyncrasies that can be considered paradoxical when compared to mammalian processes. Interestingly, from the relatively sparse literature, the variations occur within the realm of pain perception and responses.